Cоmmоn sеnsе аpprоаch in vоcаbulаry building оf Еnglish lаnguаgе - Utemisov, Е.Е. (KSU Publ., 2011)
This article shows ways of developing vocabulary building in English language. It consists of some efficient points like, correct selection of taught vocabulary and ways of teaching it. Moreover, using and perfectioning new vocabulary through reading. Not only examples of developing exercises can you find, but also definite influence factors on everlasting memory of vocabulary in students’ minds. Furthermore, we tried to show that it is impossible to remember words learnt by heart without understanding and using them. As a result we can surely cite that the best way of teaching vocabulary is using it in reading.
Ағылшын тілінде сөз байлығын дамытудың жалпы жолдары
Keywords: student; language; vocabulary; activity; approach; reading; writing; newspaper; collocation; grammar